Internal migration patterns of Turkey - Filiz, Şükriye Elif (My University, 2008)
Bu çalışmanın amacı Türkiye’de iç göç yollarını araştırmaktır. Çalışmanın temel sorusu 1980’ler sonrasında göç yollarında doğu-batı ve kır-kent ekseninde bir değişme olup olmadığıdır. Bunun yanında, iç göçün temel motivasyonu olduğu iddia edilen ekonomik sebeplerin Türkiye’de geçerli olup olmadığı araştırılmıştır. Tüm çalışma için veri Türkiye İstatistik Kurumu tarafından düzenlenen 1980, 1985,1990 ve 2000 nüfus sayımlarından elde edilmiştir. Bölgeler arası göç matrisleri bu nüfus sayımlarından direk hesaplama yöntemi ile elde edilmiştir. Ayrıca, bölgelerin toplam içersindeki payları da incelenmiştir. Göç yolları hem tüm ülke hem de karşılıklı bölge ilişkileri dikkate alınarak bu matrisler ile belirlenmeye çalışılmıştır. Bunun yanında, göçün nedenleri de bu matrislerle Nuts2 düzeyinde hem temel hem de genişletilmiş Gravity Modeli ile tahmin edilmiştir. Tezin genel bulguları göç yollarında değişme olduğu yönündedir. Türkiye’nin batısı hala göç edenler için çekicidir. Ayrıca, ekonomik etkenler ve eğitim sağlık gibi nedenler göçün belirleyicisi olarak anlamlı bulunmuştur. Yolları, Göçün Nedenleri, Gravity Modeli

The objective of this study is to investigate the internal migration patterns of Turkey in order to determine whether there is a change in the dominance of the east-to-west and the rural-to-urban oriented migration flows since 1980s. Furthermore, the economic motives, which are claimed to be the fundamental reason of internal migration in Turkey, are investigated in order to examine the validity of this claim. The data is obtained from the 1980, 1985, 1990 and 2000 general censuses of populations which are organized by the Turkish Statistical Institute are used in the study. To achieve the goals, the study employed interregional migration flow matrices which are measured by direct technique. In addition, the share of regions in each flows are examined. The migration patterns are investigated by considering the overall flows of country and cross relations of regions. Furthermore, the determinants of migration are investigated with basic and extended Gravity Model which considers the overall migration flow matrices by Nuts2 regions. The thesis concludes that there are some changes in the patterns of migration flows. Western Turkey is still the region that attracts migrants. Furthermore, it is concluded that the economic motives are significant as determinants of migration, and the health and education facilities appear to have an important role. Internal Migration, Migration Patterns, Determinants of Migration, Gravity Model
Keywords: Ekonomi; Göç Yolları; Gravity Modeli; İç Göç